Prevalence of Giardia lamblia in Asymptomatic Patients by Direct Examination and ELISA Methods: Fadia Abd Al-Muhsin AL-Khayat1 , Farah Thamer Abdullah2 and Najwa Shhab Ahmed2 - AL-Khayat, Fadia Abd Al-Muhsin (The Iraqi Journal of Veterinary Medicine, 2015)
Stool samples from 182 asymptomatic patients were collected from two hospitals in Baghdad (Al-Yarmok and Central Child) during the period from the beginning of March to the end of June/2014 and subjected to microscopic and ELISA diagnostic techniques for Giardia lamblia detection; the sensitivity and specificity for ELISA were calculated. Cysts of G. lamblia were observed in 37 and 49 stool samples of asymptomatic patients from a total 182 examined samples with prevalence recorded 20.32, 26.92% by direct examination and ELISA respectively. Of 145 samples showed negative result in microscope examination, 12 samples were positive in ELISA, sensitivity and specificity of ELISA were 75.51 and 100%. Higher prevalence rates were observed in asymptomatic children aged 2-8 years old 27.84% (22+ve/79) in contrast with 26.21% prevalence rate in asymptomatic adults aged 21-57 years old (27+ve /103). According to gender, males showed higher prevalence 28.94% (33+ve/114) while females showed lower prevalence rate 23.52% (16+ve/68). No differences in the level of infection in both age and gender were recorded. Conclusion: The superior sensitivity of the rapid enzyme assay in detecting asymptomatic cases of giardiasis when a single stool specimen is analyzed, the availability of an immunodiagnostic assay which can detect small amounts of antigens in the feces which have a potential tools to improve the diagnosis.